Microsurgical revascularization of a symptomatic proximal vertebral artery: pilot experiences from a single center - Zhang, Tongfu; Zhou, Donglin; Xu, Yangyang; Li, Maogui; Zhuang, Jianfeng; Wang, Hai; Zhong, Weiying; Chen, Chao; Kuang, Hong; Wang, Donghai; Wang, Yunyan (Frontiers in Neurology, 2023)
Background Vertebral artery stenosis and occlusion (VASO) is a high-risk factor for posterior circulation stroke. Post-stent restenosis and drug tolerance have facilitated the exploration of microsurgical vascular reconstruction. This study aims to evaluate the safety and efficacy of microsurgical reconstruction of the proximal VA. Methods Twenty-nine patients (25 men, aged 63.2 years) who had symptoms of posterior circulation ischemia underwent microsurgical revascularization for proximal VASO were retrospectively included in this study. Procedural complications and clinical and angiographic outcomes were reviewed. Results Twelve, three, and five patients underwent VA endarterectomy, artery transposition, or both, respectively; seven patients underwent vertebral endarterectomy plus stent implantation; and two patients failed surgery because of the difficult exposure of the VA and the occurrence of vascular dissection. The perioperative period-related complications included seven cases of Horner’s syndrome, five cases of hoarseness, and one case of chylothorax. No cases of perioperative stroke or death were reported. The mean follow-up period was 28.4 (8–62 months). Most patients improved clinically; however, the vertebrobasilar ischemia symptoms did not decrease significantly in two patients during the follow-up. Moreover, follow-up imaging was performed in all the patients, and no signs of anastomotic stenosis were reported. Conclusion Microsurgical reconstruction is an alternative option that can effectively treat refractory proximal VASO disease and in-stent stenosis, with a high rate of postoperative vascular recirculation. Prospective cohort studies with larger sample sizes must be conducted to validate the above conclusions.